2015
DOI: 10.36321/kjns.vi20151.3150
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Knowledge and Attitudes towards Health Promotion At Al-Hussein Medical City in Kerbela

Abstract: Objectives: to assess nurses’ knowledge and attitudes toward health promotion at Al-Hussein medical city in Kerbela. Methodology: A descriptive study was carried out during the period of March 25th through June 30th, 2014 to assess the nurses’ knowledge and attitudes toward health promotion at Al-Hussein medical city in Kerbela on a sample of 120 nurses. A questionnaire was used in the study, which contain information about the demographic data of the nurses (5 items) & selected questions about their knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Moreover, nurses with a bachelor’s degree scored higher in attitude than those with an associate degree. Likewise, a cross-sectional study of 120 Iraqi nurses showed positive attitudes toward public health activities ( 42 ). Most participants (88.3%) believed they should be more responsible for promoting health, 59.1% had sufficient time to carry out health promotion activities, and 53.3% felt confident in their abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nurses with a bachelor’s degree scored higher in attitude than those with an associate degree. Likewise, a cross-sectional study of 120 Iraqi nurses showed positive attitudes toward public health activities ( 42 ). Most participants (88.3%) believed they should be more responsible for promoting health, 59.1% had sufficient time to carry out health promotion activities, and 53.3% felt confident in their abilities.…”
Section: Introductionmentioning
confidence: 99%